Migrating Birds Optimization: A new metaheuristic approach and its performance on quadratic assignment problem - ALKAYA, ALİ FUAT (ELSEVIER SCIENCE INC, 2012)
We propose a new nature inspired metaheuristic approach based on the V flight formation of the migrating birds which is proven to be an effective formation in energy saving. Its performance is tested on quadratic assignment problem instances arising from a real life problem and very good results are obtained. The quality of the solutions we report are better than simulated annealing, tabu search, genetic algorithm, scatter search, particle swarm optimization, differential evolution and guided evolutionary simulated annealing approaches. The proposed method is also tested on a number of benchmark problems obtained from the QAPLIB and in most cases it was able to obtain the best known solutions. These results indicate that our new metaheuristic approach could be an important player in metaheuristic based optimization. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Metaheuristics; Optimization; Birds' migration; V-shape topology; Benefit mechanism; HYBRID GENETIC ALGORITHMS; FORMATION FLIGHT; DIFFERENTIAL EVOLUTION; ENERGY SAVINGS; SEARCH; FORMULATION